2022
DOI: 10.21037/qims-21-520
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization and clinical significance of biventricular mechanics in patients with systemic lupus erythematosus by 3T cardiovascular magnetic resonance tissue tracking

Abstract: Background: Detecting impaired left ventricle (LV) or right ventricle (RV) mechanics could aid in fully understanding the process of cardiac involvement in patients with systemic lupus erythematosus (SLE). This study aimed to evaluate biventricular strain parameters derived from cardiac magnetic resonance (CMR) tissue tracking in SLE patients and their association with other clinical variables.Methods: A group of 47 SLE patients and 27 healthy controls were enrolled and underwent CMR examination, including cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Few case-control studies have reported of RV-volumes in SLE-patients. A recent case-control study by Pu et al [ 49 ] found no difference in RV-volumes. Our findings on this might be due to healthy controls being more physically active or an actual SLE-related pathophysiological mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…Few case-control studies have reported of RV-volumes in SLE-patients. A recent case-control study by Pu et al [ 49 ] found no difference in RV-volumes. Our findings on this might be due to healthy controls being more physically active or an actual SLE-related pathophysiological mechanism.…”
Section: Discussionmentioning
confidence: 95%